"تصميم هوية بصرية لمنتجات تقليدية "تمريات لينة - زاير, محمد (مكتبة كلية الأدب العربي والفنون, 2023)
يهدف هذا البحث الى تصميم هوية بصرية لشركة مواد غذائية تقليدية"تمريات لينة"، حيث قمت بتصميم تغليف للمنتج بجميع لواحقه الفنية التسويقية. وقد إعتمدت على المنهج الوصفي التحليلي في شرح المعطيات والعناصر التي تدخل في تصميم الهويةالبصرية This research aims to design a visual identity for a traditional food company called 'Tamriyat Lena'. I have designed and used the descriptive-analytical approach, which helped me in explaining the data and elements I used in designing this identity. I have reached some results in my study that demonstrated the impact of this identity on the audience.
Keywords: هوية برصية؛ كة موإد غذإئية تقليدية ؛ تمريات لينة؛ تصميم؛ تغليف؛ تأثري; Visual Identity; Traditional Food; “Tamriyat lena”; Design; Packaging; Impact